2009
DOI: 10.1109/tvcg.2009.194
|View full text |Cite
|
Sign up to set email alerts
|

Verifiable Visualization for Isosurface Extraction

Abstract: Fig. 1. Through the verification methodology presented on this paper we were able to uncover a convergence problem within a publicly available marching-based isosurfacing code (top left) and fix it (top right). The problem causes the mesh normals to disagree with the known gradient field when refining the voxel size h (bottom row). The two graphs show the convergence of the normals before and after fixing the code.Abstract-Visual representations of isosurfaces are ubiquitous in the scientific and engineering l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…However, Etiene et al [17] recently have pointed out that asymptotic error measures can be more powerful in finding problems in an implementation.…”
Section: Validation Verification and Reproducibilitymentioning
confidence: 99%
“…However, Etiene et al [17] recently have pointed out that asymptotic error measures can be more powerful in finding problems in an implementation.…”
Section: Validation Verification and Reproducibilitymentioning
confidence: 99%
“…Visualization algorithms should be subject to the same verification process that is used in other components of the scientific pipeline-this is also called verifiable visualization [35]. We expect that semi-automatic verification techniques, such as fuzzing, could greatly benefit from generative models due to extra knowledge about the parameter space.…”
Section: Verificationmentioning
confidence: 99%
“…Globus and Uselton [11] first pointed out the need to verify not only visualization algorithms but also their implementations, and Kirby and Silva suggested a research program around verification [18]. The verification of isosurface algorithms was discussed by Etiene et al [8], [9], where a systematic evaluation identified and corrected problems in several implementations of isosurface extraction techniques. Zheng et al [47] address CT reconstruction and interpolation errors in direct volume rendering algorithms using a verifiable framework based on projection errors.…”
Section: Related Workmentioning
confidence: 99%
“…The error computation and analysis will proceed differently depending on whether an analytical solution for the VRI is available or not. We highlight that previous frameworks for verification of visualization algorithms could benefit from the fact that analytical solutions can be easily constructed [9]. For the case of the VRI, this is no longer true, and therefore we should not rely on known solutions.…”
Section: Convergence Computationmentioning
confidence: 99%